Design interventions to repair migrants' mental well-being: The 'Culture in Mind' healing space. Issue 2 (1st October 2018) - Kalantidou, Eleni
The intention of this article is to present the transformation of a space that houses a migrant-oriented community service with a focus on mental health and well-being (Culture in Mind) into an inviting milieu, which fosters healing processes, intercultural understanding and community empowerment in Brisbane, Australia. This project, which was formed as a case study, is described through its ideation phase, the installation methods, the sourcing and use of reclaimed materials as well as the methods employed for the collection of data, including interviews conducted for the evaluation of the design interventions. In like manner, the outcomes of the data analysis are discussed in conjunction with evidence provided by relevant studies and photos collected through the documentation process. The final part of the article is dedicated to arguing the necessity of different understandings of mental health according to non-western cultural backgrounds so as to inform the design of mental health services and physical settings and enhance sentiments of privacy, safety and dignity for migrant patients.